Contradictions of the “legendary city”: an analysis of the poetic production of Jomard Muniz de Britto (PerCursos, 2023)
This analysis seeks to understand the tension between tradition and modernism that cross the poetic productions of Jomard Muniz de Britto about the city of Recife-PE. Paying attention to the production of a literature of resistance, of confrontation, which seeks to create another language, another way of seeing/thinking and saying about city relations not only through its content, but also its form. In this sense, we first observe Jomard’s creative process, thought around what the author calls the “língua dos Três Pppês”, through interviews, especially organized in the book by Sérgio Cohn (2013), and books by the author, such as Contradições do homem brasileiro (1964), Do Modernismo à Bossa Nova (1966) and Atentados Poéticos (2002), to then delve more precisely into his poetic production, around the books: Terceira Aquarela do Brasil (1982) e Arrecife de Desejo (1994).
Keywords: history of Brazil; literature; counterculture; Jomard Muniz de Britto